Editorial - Del Cimmuto, Angelo; Benussi, Fulvio Oscar (Community Notebook. People, Education and Welfare in the Society 5.0, 2024)
In today's society (variously named, post-industrial, post-modern, high-technology-high-communication, interconnection, ICT, social web) the full and total affirmation of first electronic technology and then digital culture, the latter being closely related to the former, have led to the exponential growth of information and communication processes, which have quickly become necessary and strategic for the development and subsistence of public policies and practices dedicated to the organisation of societies and the management-planning of activities aimed at education and training.